The use of mazes over time in Spanish heritage speakers in the US - Martinez-Nieto, Lourdes; Moen, Theresa; Pierce, Melissa; Restrepo, Maria Adelaida (Frontiers in Psychology, 2023)
Mazes are linguistic disfluencies such as repetitions, filled pauses, or revisions of lexical, grammatical, or phonological aspects of words that do not contribute to the meaning of a sentence. Bilingual children are believed to increase the numbers of mazes in their native or heritage language, the minority language, as they become more proficient in the second language, the societal language. In the US, mazes may be more pronounced in Spanish-speaking children as they typically become more proficient in English, although most studies are not conducted longitudinally. Higher rates of mazes in the heritage language may also be due to changes in language proficiency and differences in processing demands in the children as they use more complex language. However, children with developmental language disorder (DLD) can also present higher rates of mazes than children with typical language. Heritage speakers, therefore, are at risk of being misdiagnose if we do not understand what the typical rates of mazes are as they get older and more proficient in the societal language. The current study aimed to examine the type and frequency of Spanish mazes longitudinally in a group of 22 Spanish heritage speakers (HS) with and without DLD and determined the changes over time.